Sosialisasi Potensi Bencana dan Sistem Informasi Geografi (SIG) Kebencanaan di Kabupaten Seluma - Supriyono Supriyono; Dedi Guntar; Edwar Edwar; Zairin Zairin; Warsa Sugandi (Universitas Muhammadiyah Pringsewu, 2018)
Knowledge and understanding of geographic information systems (GIS) in the field of disaster, GIS can provide a spatial visualization of the potential and mitigation. In implementing this devotion Seluma has a high potential for disaster. So the role and knowledge of GIS in Determining the potential for disaster in Seluma need to be socialized and simulated in order to provide a general description of potential disasters and SIG. GIS in disaster mapping capability to provide trend geographic information that can be understood and support the process of decision making in disaster. Socialization and simulation in service activities aim to: equip public knowledge of potential disasters and provide disaster mitigation efforts of community-based alternatives were alert, responsive and resilient to disasters. Service activities performed by a lecture and demonstration. Lecturing to socialize about potential disasters and GIS. Demonstration method to implement community-based disaster mitigation simulation. The results of the simulation activities of dissemination and disaster mitigation in the Cahaya Negeri Village, Sukaraja District of Seluma country, the regions most vulnerable to disasters is a top priority in mitigation measures. GIS for disaster preparedness is effective as a means of equipping the public knowledge of potential disasters and provide disaster mitigation efforts of community-based alternatives were alert, responsive and resilient to disasters. Judging from the success of the socialization of the target number of participants (85%), achievement of the objectives of socialization (72%), achievement of the target material that has been planned (78%), and the ability of the participants in the mastery of the material (70%). The success can also be seen from the satisfaction of participants socialization and simulation.Keywords: Socialization and Simulation, Disaster Potential and GIS